Framework For The Development And Evaluation Of Electronic Commerce In Malaysia - Poong, Yew Siang (2008)
This study, however, attempts to explain consumers' attitude towards e-commerce. This research examines the effects of perceived relative advantage, perceived compatibility, perceived ease of use, perceived result demonstrability and perceived visibility on intention to use e-commerce. In addtion to these characteristics, this research also integrates perceived trust to the perceived innovation characteristics.